International financial stabilization : a symposium - Irving Trust Company; Shields, Murray; Bogen, Jules Irwin; Irving Trust Company (New York, N.Y., Irving Trust Company, 1944)
The book presents the post-Bretton Woods views of six distinguished American monetary economists together with a review of the proposals, reprinted from the Federal Reserve Bulletin, and the full text of the agreements on international financial stabilization.
rua 21/04/17
Loans.
Keywords: Currency question; Financial stabilization; Financial Conference